HEG1 as a novel potential biomarker for the prognosis of lung adenocarcinoma - Xin Zou; Yue Zhang; Ning Wang; Jie Shi; Qinghai Li; Wanming Hao; Wenjing Zhu; Wei Han (Cancer Medicine)
Abstract Background Heart development protein with EGF‐like domains 1 (HEG1), generally related to angiogenesis and embryonic development, was reported to participate in the occurrence and progression of some tumors recently. However, the role of HEG1 in lung adenocarcinoma (LUAD) is unclear. Patients and Methods To explore the effect of HEG1 on LUAD, GEPIA platform and UALCAN database, as well as Kaplan–Meier plotter were adopted to analyze the association of HEG1 with clinicopathological characteristics and survival outcomes for LUAD firstly. And then the HEG1 in LUAD tissues, blood and cell lines were detected by qRT‐PCR, western blot, immunofluorescence, immunohistochemistry, and ELISA. Gene set enrichment analysis (GSEA) was conducted to identify pathways that might be affected by HEG1 in LUAD. Results In this study, HEG1 in lung tissues and cell lines of LUAD were significantly downregulated compared to benign pulmonary disease tissues and alveolar epithelial cells (p < 0.05). Moreover, compared with other groups, patients with advanced tumor stage had lower HEG1 mRNA expression levels (p = 0.025), which were negatively correlated with Ki67 index in tumor tissues (r = −0.427, p = 0.033). On the other hand, the LUAD patients with lower HEG1 had shorter overall survival (OS) (HR = 0.51, 95% CI: 0.40–0.65, p < 0.001) according to Kaplan–Meier plotter. In addition, HEG1 in serum of LUAD patients was negatively associated with CEA (r = −0.636, p < 0.001). GSEA showed that HEG1 was enriched in various metabolic‐related pathways, including glucose metabolism, lipid metabolism, and nucleotide metabolism signaling. Conclusions HEG1 was downregulated in LUAD patients and associated with poor prognosis, which indicating HEG1 may serve as a potential biomarker for diagnosis and prognosis of LUAD.